Dhikr in Surah Al-Baqarah Verse 152 According to Syekh Ibnu Ajibah (An Analytical Study of the Book of Tafsir Bahrul Madid) - Muhammad Abbel Saktyanugraha; Kgs. Muhammad Zaki; Mufassirotul Bayaqi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
In the contemporary era, human life is increasingly marked by anxiety and psychological unrest arising from various personal and social problems. These conditions often disturb inner peace and weaken faith. To maintain spiritual stability, Islam offers dhikrullah as a medium for continuously remembering Allah, which functions as a means of strengthening and stabilizing faith. The Qur’an emphasizes that Allah bestows divine light upon those who engage in remembrance, causing their hearts to tremble in reverence. This study aims to examine Ibnu Ajibah’s interpretation of dhikr in Surah Al-Baqarah verse 152 and to analyze its relevance in contemporary life. This research employs a descriptive-analytical method with a qualitative approach, utilizing documentation techniques by examining primary sources particularly Tafsir al-Baḥr al-Madīd as well as relevant secondary literature such as books, journals, and scholarly articles. The findings reveal that according to Ibnu Ajibah, the command to remember Allah entails remembrance performed with a pure heart, a cleansed soul, firm monotheism, and strong faith. In return, Allah remembers His servants by unveiling the heart, removing spiritual veils, elevating their spiritual rank, and granting divine assistance. Gratitude (shukr) through remembrance is emphasized as a safeguard against spiritual negligence and shirk. The relevance of this interpretation in daily life is evident in its profound impact on both psychological and spiritual well-being, manifesting as inner peace, mental stability, and authentic happiness.